Q: What is 6 - 1 x 0 plus 1?

Write your answer...

Submit

Related questions

(x + 6)(x + 1) = 0 so x = either -1 or -6

x^2+5-6=0 (x+6)(x-1)=0 x=1,-6

x3 + 4x2 + x - 6 = 0 x3 - x2 + 5x2 - 5x + 6x - 6 = 0 x2(x - 1) + 5x(x - 1) + 6(x - 1) = 0 (x - 1)(x2 + 5x + 6) = 0 (x - 1)(x + 2)(x + 3) = 0 So x = 1 or x = -2 or x = -3

When the given expression equals 0 then x = -1/6 and x = -6

x2 - 7x + 6 = 0(x - 6)(x - 1) = 0x = 6, x = 1

x2 + 5x =6 x2+5x -6 = 0 (x+6)(x-1) = 0 x+ 6 = 0 x = -6 x-1 = 0 x = 1

x2 + 5x + 3 = 9 x2 + 5x - 6 = 0 (x + 6)(x - 1) = 0 x = -6 or x = 1

X + (-6) = 0 x = 6 6 is the answer

x=-6+6=0 then x=-2+2=0 and 0+0=0

x2- 7x + 6 = 0 factor, (x-6)(x-1) = 0 x = 6 x = 1

x2 + 7x + 9 = 3 ∴ x2 + 7x + 6 = 0 ∴ (x + 6)(x + 1) = 0 ∴ x ∈ {-6, -1}

x2 + 12x + 36 = 0(x + 6) (x + 6) = 0x+ 6=0 ;x + 6 = 0x = -6 ; x = -6

2x2 = 10x + 12 2x2 - 10x - 12 = 0 x2 -5x -6 = 0 x2 - 6x + x - 6 = 0 x(x -6) + 1(x -6) = 0 (x+1)(x-6) = 0 x = -1 or x = 6

0

2 x 0 x 1 + 1 = 0 + 1 = 1

x^2 + 12x + 36 = 0(x + 6)(x + 6) = 0(x + 6)^2 = 0√(x + 6)^2 = ± √0x + 6 = 0x + 6 - 6 = 0 - 6x = 6

x2 + 2x -6 = 0 x2 + 2x + 1 = 7 (x + 1)2 = 7 x = -1 ± √7

X + 1 - x - 1 = 0, for all x. Regroup: (x - x) + (1 - 1) = 0 + 0.

If you mean: x2+5x+6 = 0 then the solutions are x = -3 and x = -2

9x-53=6/x 9x2-53x=6 9x2-53x-6=0 9x2+x-54x-6=0 x(9x+1)-6(9x+1)=0 (9x+1)x(x-6)=0 9x+1=0 or x-6=0 9x=-1 or x=6 x=-1/9 or x=6

(because zero time 1= 0 plus 1)

x4 + 3x3 - x2 - 9x - 6 = 0 x4 + x3 + 2x3 + 2x2 - 3x2 - 3x - 6x - 6 = 0 x3(x + 1) + 2x2(x + 1) - 3x(x + 1) - 6(x + 1) = 0 (x + 1)(x3 + 2x2 - 3x - 6) = 0 (x + 1)[x2(x + 2) - 3(x + 2)] = 0 (x + 1)(x + 2)(x2 - 3) = 0 So x + 1 = 0 so that x = -1 or x + 2 = 0 so that x = -2 or x2 - 3 = 0 so that x = +/- sqrt(3)

Yes and its solutons are: x = -1 -sq rt of 6 and x -1 +sq rt of 6

the answer is : 06 x 6 + 6 x 0, if you follow the order of operations, is (6 x 6) + (6 x 0), which is 36+0, which is 36

solving for the x variable given that x2-6x+5=0 factoring the polynomial gives (x-1)(x-5)=0 which leaves you with your two answers, x=1, 5 or you could have used the quadratic equation x = [ -(-6) plus/minus sqrt( (-6)2 - 4*1*5 ) ] / (2*1) x = [ 6 plus/minus sqrt( 36-20 ) ] / 2 x = [ 6 plus/minus 4 ] / 2 x = 3 plus/minus 2 x = 5, 1

Study guides